Alterações retinianas na doença de Parkinson, demência com corpos de Lewy, demência frontotemporal e demência vascular: revisão sistemática - Renata Caroline Ferreira Gomes (2024)
Parkinson's disease (PD), dementia with Lewy bodies (DLB), frontotemporal dementia (FTD), and vascular dementia (VD) are significant causes of dementia that negatively affect the ability to perform daily activities, such as domestic, occupational, social, or leisure tasks. These neurodegenerative and vascular conditions often present diagnostic challenges due to overlapping symptoms, especially in the early stages. Advances in ophthalmic imaging, such as optical coherence tomography (OCT), offer promising non-invasive biomarkers for early diagnosis. This systematic review aimed to investigate retinal changes in PD, DLB, FTD, and VD using optical coherence tomography (OCT) as a diagnostic tool. A detailed search strategy was employed across three databases: PubMed, Scopus, and Scientific Electronic Library Online (SciELO), with article selection based on inclusion and exclusion criteria, followed by data extraction and descriptive analysis. The search yielded 235 articles, of which 78 were selected for review. Turkey had the highest number of publications, and the average impact factor of the journals was 3.6. To assess the retina, the thickness of the nerve fiber layer around the optic disc and the central macular region were considered. The retinal layers evaluated included the nerve fiber layer around the optic disc and the central macular region. Most studies either did not present the significance value of the thickness differences between patients and controls or did not demonstrate a statistically significant difference. A significant limitation in the analyses was observed due to the heterogeneity of study methodologies. It is concluded, therefore, that although some recent studies suggest that changes in retinal layer thickness may reflect neurodegenerative and vascular processes, further studies are necessary to determine whether retinal changes can serve as potential biomarkers in these neurodegenerative diseases. Prospective research with methodological standardization is imperative.